The Development and Validation of a Measure of Health-Related Quality of Life for Non-Hodgkin's Lymphoma: The Functional Assessment of Cancer Therapy—Lymphoma (FACT-Lym). (20th February 2013) - Hlubocky, Fay J.; Webster, Kimberly; Cashy, John; Beaumont, Jennifer; Cella, David
Abstract : Background . The individual concerns of non-Hodgkin's lymphoma (NHL) patients require identification and assessment during clinical research proposing to measure patients' outcomes. The FACT-Lym was developed as part of the FACIT measurement system to address health-related quality-of-life (HRQL) issues for NHL patients. Patients and Methods . Items for the FACT lymphoma subscale (LymS) were generated from healthcare provider interviews, published literature, and content validity patient interviews. The FACT-Lym was validated on a sample of 84 NHL patients, with additional measures at baseline (T1), 3–7 days (T2), and 8–12 weeks (T3). Results . Item correlations, expert relevance ratings, and patient input on content shortened the initial 22-item LymS to 15 items. The validation sample included 56% female, 76.2% white, 60% indolent disease, and 85% receiving treatment. Internal consistency coefficients for the 15-item LymS (.79, .85, and .84 T1–T3) and test-retest stability (.84) indicated good reliability. Correlations between LymS and SF-36 physical (r = .62 ) and mental (r = .48 ) summary scores reflect concurrent validity. Responsiveness to ECOG performance status and treatment status exceeded established FACT subscale scores. The FACT-LymS differentiated patients' retrospective ratings of change in each of the three groups (better; unchanged; worse), P < 0.001 . Conclusions . These results support the validity of the FACT-Lym and suggest it will be a useful targeted endpoint in NHL clinical research.